Offshore subsurface characterization enabled by fiber-optic distributed acoustic sensing (DAS): An East China Sea 3D VSP survey example - Chen, Yuanzhong; Zong, Jingjing; Liu, Chengxin; Cao, Zhonglin; Duan, Pengfei; Li, Jianguo; Hu, Guangmin (Frontiers in Earth Science, 2023)
Recent advances in distributed acoustic sensing (DAS) technology have allowed more intense measurements of subsurface and environment events, providing improved geohazard monitoring and subsurface characterization. This study discussed the subsurface evaluation enabled by the DAS-vertical seismic profiling (DAS-VSP) system in the East China Sea, China. Taking advantage of a continuous recording of the vibrational wavefields through the strain deformation of the fiber deployed along the borehole, DAS-VSP is considered an emerging and promising alternative borehole acquisition method. It provides a wider-spectrum range of recordings in a cheaper, denser, and more continuous tense compared to conventional geophones. We explored the 3D DAS-VSP signal processing and imaging strategy. Based on a set of 3D DAS-VSP data of exceptional quality, this study reviewed the common processing challenges and practical solutions for de-noise, de-ghosting, de-multiple, and wavefield separation arising from the DAS acquisition mechanism in the offshore VSP scenario. High-quality down-going multiples were separated and imaged using the pre-stack Gaussian beam depth migration in addition to the primary reflection wavefield, providing significant additional illumination to support the subsurface evaluation. The current results validated the efficiency of the DAS-VSP survey and encouraged better geological interpretation.